Sistem Aplikasi Pendukung Keputusan Menggunakan Metode AHP Dalam Menentukan Kinerja Pegawai Kantor Desa Suka Maju Deli Serdang - Sitanggang, Rianto; Manurung, Immanuel H. G.; Sibero, Alexander F.K.; Khair, Husnul (JUKI : Jurnal Komputer dan Informatika, 2024)
Performance assessment is something that must be done by a company, whether private or public. Performance appraisal can provide rewards or punishment for an employee's performance based on whether the work they do is good or bad. The assessment carried out in this research was implemented by creating a system which was carried out using one method, namely AHP (Analytic Hierarchy Process). The measurement process is carried out by applying the waterfall method. The results of research carried out by applying the AHP decision support system method can provide efficient results and the level of data accuracy is close to perfect.